DEVELOPMENT OF A LEARNING MANAGEMENT PLAN IN SPORTS AND RECREATION ACCORDING TO THE CONCEPT OF SAM SPORT ACTIVITY IN GRADE 6 AT ANUBAN MUANG MAI CHONBURI SCHOOL - Hirankitidecho, Phacharaphon; Maharkan, Pattarapon; Sumbandit, Weena (Academic Journal of Thailand National Sports University, 2023)
The purpose of this research was to develop a plan for sports and recreation learning activities according to the concept of SAM Sports Activity in grade 6 at Anuban Muang Mai Chonburi School and to assess plans for learning sports and exercise activities based on the SAM sports activity concept. The sample group used in this study consisted of 15 primary school student’s grade 6, Muang Mai Kindergarten, Chonburi. The research instrument was: - 1) a learning management plan, based on the concept of SAM Sport Activity, 2) the assessment form for the learning management plan, 3) the knowledge test before and after participating in the activity, 4) a student behavior observation form, and 5) attitude level before and after participating in the activity. The collected data were analyzed by percentage, mean, standard deviation, effectiveness index and paired sample t - test. The result of the study revealed that: - 1) developing a learning management plan in sports and recreation according to the concept of SAM Sport Activity should focus on 3 aspects of activities, namely sports (S), art (A), and music (M) in organizing learning activities. 2) Comparison of preschool and post-school exam scores on knowledge (K), behavior (P), and attitude (A) before and after school according to the student's sports and recreation management plan according to the concept of SAM Sports Activity after studying, it was significantly higher than that before at the .05 level. 3) Observation of students’ behavior, the students had the courage to express themselves, had imagination, and were happy with the activities and better movement. 4) Activities based on the concept of SAM Sports Activity help students develop the use of the right brain, encourage the use of imagination, creativity, and assertiveness to be happy and participate in activities. In addition, learning by doing promoted the development of knowledge, behavior and attitude.